Endoscopic Multiportal Approaches to Meckel's Cave: A Cadaveric Study and a Three-Dimensional Anatomical Video - Salem, Eman H.; Abd El-Fattah, Ahmed Musaad; Ebada, Hisham Atef; Koevering, Kyle van; Hardesty, Douglas A.; Prevedello, Daniel M.; Al-Saddeik, Mohamed Abd El-halem; Carrau, Ricardo L. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objective This cadaveric study aims to illustrate the lateral transorbital (LTO), transantral transpterygoid (TATP), and endoscopic endonasal approaches (EEA) to Meckel's cave (MC), defining their surgical freedom, area of exposure, and advantages and limitations; thus, refining their respective indications.Design Cadaveric study.Setting The Anatomical Laboratory for Visuospatial Innovations in Otolaryngology and Neurosurgery (ALT-VISION) at the Ohio State University, Wexner Medical Center.Participants Bilateral dissections of five injected cadavers (10 sides).Main Outcome Measures Distance to targets, surgical freedom, and area of exposure provided by the EEA, TATP, and LTO approaches.Results The TATP approach provides superior surgical freedom to foramen rotundum (167.70 ± 29.762 mm). However, surgical freedom to foramen ovale was best when using the LTO approach (75.01 ± 15.773 mm). The EEA provides a superior exposure of the medial MC (mean area of 587.69 ± 38.59 mm2). The LTO and TATP approaches provide equivalent access to the lateral MC (ranging from 468.90 ± 26.98 mm2 for TATP to 650.11 ± 35.76 mm2 for the LTO approach). Combining approaches increases the area of exposure significantly (1,237.79 ± 48.41 mm2 and 1,056.59 ± 48.12 mm2 for EEA and LTO vs. EEA and TATP).Conclusion This study thoroughly emphasizes the pros and cons of the aforementioned approaches. Each approach may be applied in selected cases as a single or as part of a combined technique. However, conventional approaches are still indicated according to extent and pathology.Level of Evidence: V.
Keywords: Meckel's cave; transorbital; transpterygoid; endoscopic endonasal; multiportal